PHRASEOLOGY AND ITS USE IN MODERN SPEECH - Sattarova Firuza Ulugbekovna; Zhurayeva Madinakhon Bakhodir kizi (Western European Studies, 2024)
Russian phraseology's versatility indicates, first of all, a rich historical heritage, reveals an incomprehensible Russian soul, because it is not by chance that most phraseological units have come to life among the people. Mastering this cultural "archive" allows you to comprehend the lives of people of various strata in a particular era, their richness of language and the power of meaning, and therefore is necessary for every educated person
Keywords: phraseology; phraseological units; phrase; stable combinations